(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
Encontros Bibli Vol. 17, n. Esp. 2 (2012) Link de acesso ao número https://periodicos.ufsc.br/index.php/eb/issue/view/1927/showToc